The Search for Truth and the Means of Proof: The Investigation of the Case and the Statement of the Parties and the Testimonial Evidence - Morán Bustos, Carlos M. (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2021)
Marriage annulment proceedings are an instrument aimed at ascertaining the truth of the marital bond; a task that is not easy and that requires the use of all means to examine the historical truth better. To discover the truth, to enquire into it and to bring it to light — especially the truth of historical facts — it is essential that the preliminary investigation is conducted correctly. This explains the need to focus on the means of evidence, since they have a great potential as instruments for ascertaining the factual truth. Leaving aside expert evidence, reference is made to parties’ statements, emphasizing on the way they are carried out in the investigation phase, rather than on its evaluation. Above all, the reflection focuses on the evidence of witnesses, since they are frequent means of evidence used in canonical marriage annulment proceedings regarding which little canonical literature is available. The analysis carried out deals with issues such as the witness’ notion, the object of their statements, the witness’ duty to testify and to tell the truth, the dynamics of witness evidence, and especially, the criteria to evaluate the statements that are set forth in cc. 1572-1573: firstly, to analyze the state of the person and his/her honesty; secondly, to see if the witness testifies mainly from his/her own knowledge, either from what he/she has seen or heard, or if the witness expresses his/her opinion, a common awareness or what the witness has heard from others; thirdly, if the witness is constantly and firmly coherent, or if he/she is variable, insecure or doubtful; fourthly, if there are non-dissenting statements or whether the statement is confirmed by other evidence.